2015
DOI: 10.1074/jbc.m115.657072
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of N-Glycoforms in Human Chorionic Gonadotropin by Monoclonal Antibodies and Their Interaction Motifs

Abstract: Background:The N-linked oligosaccharides of human chorionic gonadotropin become more complicated in cancer. Results: MCA1024 alters its binding affinity against different human chorionic gonadotropin glycoforms. Conclusion:The N-glycosylations at Asn-13 and Asn-30 on the ␤ subunit are crucial to the binding affinity of MCA1024. Significance: The aberrant glycosylation of cancer biomarkers might potentially be monitored by specific antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The protein N -glycosylation of biological materials is generally species specific and therefore extensively studied for its potential as biomarkers in various areas, especially in medical biology. In first studies, the identification of protein N -glycosylation has been also reported to be a reliable tool in food safety and food quality control research. ,, Our previous study also showed that significant N -glycan structural difference was found between human milk and bovine milk . These findings suggest the idea that N -glycan profiles may be of interest for meat-species-specific biomarker and therefore can be used as a tool in meat authentication.…”
Section: Discussionmentioning
confidence: 95%
“…The protein N -glycosylation of biological materials is generally species specific and therefore extensively studied for its potential as biomarkers in various areas, especially in medical biology. In first studies, the identification of protein N -glycosylation has been also reported to be a reliable tool in food safety and food quality control research. ,, Our previous study also showed that significant N -glycan structural difference was found between human milk and bovine milk . These findings suggest the idea that N -glycan profiles may be of interest for meat-species-specific biomarker and therefore can be used as a tool in meat authentication.…”
Section: Discussionmentioning
confidence: 95%
“…They have been reported to consist mainly of mono-and bi-antennary complex type structures with terminal sialic acid and with or without core fucosylation [1,17,24,25]. Some glycans have been specifically associated with malignancy [26][27][28]. For example, increases in tri-antennary N-glycans have been linked to hCG from tumour cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…Three aspects of hCG glycosylation are not well understood. First, the glycosylation of hCG from healthy pregnant women is not well defined because studies employing sophisticated analytical methodologies have usually focused on the more abundant hCG expressed by trophoblastic tumours [27,30]. Second, not much is known about the glycosylated forms (glycoforms) of hCG that are synthesised during obstetrical syndromes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alpha subunit contains 2‐N‐linked glycosylation sites at amino acids 52 and 78 and the beta subunit contains 2‐N‐linked glycosylation sites at amino acids 13 and 30 and 4 O‐linked glycosylation sites at amino acids 121, 127, 132, and 138. 6 , 7 The hCG and luteinizing hormone (LH) shows similar molecular structures and interact with the same LH/chorionic gonadotropin (CG) receptor. 8 As a result of this similarity to LH, hCG is used pharmacologically in a number of clinical indications.…”
Section: Introductionmentioning
confidence: 99%